Herbal usage in cancer management in traditional and complementary unit of Putrajaya Hospital / Nur Natasha Abdullah - Abdullah, Nur Natasha (2012)
The use of traditional and complementary medicine has been rapidly increasing in developed and developing country including Malaysia. One of the widely used treatment in traditional and complementary medicine is herbal oncology. Putrajaya Hospital was one of the hospital Malaysia implement herbal oncology in traditional and complementary medicine unit. The aim of this study is to determine the percentage of cancer patients in TCM unit of Putrajaya Hospitals who took herbs in their cancer management, what types of herbs that are used, factors that influence the usage of herbs, the demography of patients with what kind of cancer who also use herbs in cancer management, as well as the role of pharmacist in providing information and advice to cancer patients on the usage of herbs in cancer management. This is a retrospective study and data on cancer patients who were referred to the TCM unit of Putrajaya Hospital was collected using data collection forms.. Data was collected from hospital records from January-October 2011. Female cancer patients made up 68% of the total number of cases studied. 87% of cancer patient in Putrajaya Hospitals were treated with herbs in TCM unit. The main reasons for using herbs in cancer management is to enhance patients' quality of life, to elicit anticancer effects of the herbs, to minimize symptoms of cancer, to relieve pain and also to reduce patients' side effects following conventional treatment which included chemotherapy. The main role of the pharmacist at TCM unit is to dispense the formulated herbs, ensured proper labeling of herbal preparations, instructions for usage, monitoring and counseling cancer patients and also were responsible for assessing patients' compliance.